Answer:
(2h-3k)(m-n)
Step-by-step explanation:
factor by grouping, you can group the first two terms and the last two terms:
2h(m-n) + (-3k)(m-n)
there will be one factor in common, use that factor in combination with the factors that are not duplicated:
(2h-3k)(m-n)
Answer:
B. ![\frac{6}{2x^{2} - 5x}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2x%5E%7B2%7D%20%20-%205x%7D)
Step-by-step explanation:
The product of the ratioal expressions given above can be found as follows:
![= \frac{2}{x} * \frac{3}{2x - 5}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7B2%7D%7Bx%7D%20%2A%20%5Cfrac%7B3%7D%7B2x%20-%205%7D%20%20)
Multiply the denominators together, and the numerators together, separately to get a single expression
![\frac{2(3)}{x(2x - 5)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%283%29%7D%7Bx%282x%20-%205%29%7D%20)
![= \frac{6}{x(2x) - x(5)}](https://tex.z-dn.net/?f=%20%3D%20%5Cfrac%7B6%7D%7Bx%282x%29%20-%20x%285%29%7D%20)
![= \frac{6}{2x^{2} - 5x}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B6%7D%7B2x%5E%7B2%7D%20%20-%205x%7D)
The product of the expression
= ![\frac{6}{2x^{2} - 5x}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2x%5E%7B2%7D%20%20-%205x%7D)
The answer is B.
Answer:
Step-by-step explanation:
The horizontal asymtote is when there are no solutions for x, so it is when y = -10.
This is because when y = -10, 0.8^x must be 0, but this is impossible. You can test this by trying 4^x/5^x. It will get super small, but never 0.
I believe that's correct.
Answer:
He mows 80 yards.
Make meh happy pls ;)
Step-by-step explanation: